Um procedimento para o estabelecimento de discriminações condicionais com o responder do sujeito como estímulo modelo - Albertazzi, Victoria Boni (2013)
Operant behavior can be placed under stimulus control, and the relationship between discriminated responding and such stimuli can also be controlled by other stimuli, generating the behavioral process named conditional discrimination. Utilizing a rat as a subject, in order to study if it s own behavior could be used as conditional stimulus, controlling choice behavior in a simulateneous discrimination, a procedure was planed based on the proposal by Lionello-DeNolf and Urcuioli (2003). After preliminary training, central lever pressing was placed under the control of a buzzer, in a procedure in which responses emmited in tone cycle accessed a reinforcer (water) and terminated the presentation of the tone, with mean intertrial intervals (ITIs) of initially 30 seconds (range 15-45s), and passing, after two sessions, for 10 seconds mean (range 5-15s). The ratio of lever presses required for water access was gradually increased, and, after reaching FR10, a mixed schedule training was implemented, in which trials with requirements of one or 10 responses were randomically presented. The subject was then placed in a matching-to-sample situation, in which two other levers were presented, and the behavior established in the previous phase accessed comparison stimuli: a blinking and a steady lights, which alternated positions randomically. With the introduction of such condition, central lever press behavior deteriorated; in trials in which comparison stimuli were accessed, choice behavior seemed to be under the control of the position of the stimuli. The role of the ITIs duration in the establishment of simple discriminations was discussed, as well as diferences in the results of such procedures with pigeons and rats